Implementation of the Student Character and Personality Determination System Using the Certainty Factor Method: Case Study: Universitas Suryakancana Cianjur - Andi Sutandi (CV. Publikasi Indonesia, 2024)
This research aims to implement a system to determine the character and personality of students using the Certainty Factor method. This method is used to analyze a student's personality based on various relevant factors. This research uses the Research and Development (R&D) method which involves data collection through surveys and observations of students whose character and personality have been identified. The system is implemented through the development of a computer-based application that integrates data and uses the Certainty Factor algorithm to analyze and determine the character and personality of students. The test results show that the system is able to provide predictions of student character and personality with a satisfactory level of accuracy. The implication of this research is that the application of information technology in the development of character and personality determination methods can make a positive contribution to the development of student personality in the academic environment.